Windows NT Server 4 = 4 - Cowart,Robert (San Francisco : Sybex, ., 1999)
This book gives you a solid foundation in Microsoft's popular network operating system, building understanding skill-by-skill and taking you from 0 to 100% in time for your next interview, performance review, or the start of your next project. The skills you need. More and more, the business world is turning to NT - for its speed, security, stability, and support for enterprise computing needs. Inside, you'll get a close look at key administration issues that, once learned, will permit you to confidently manage every aspect of your NT network. Whether you work your way through from cover to cover or head straight for what you need right now, you'll quickly learn concrete skills you can apply immediately.
Pt. I. Starting Out. 1. Evaluating NT Server's Capabilities. 2. Working from the NT Server Desktop. 3. Understanding the Anatomy of NT Server 4. 4. Designing Your NT Server. 5. Installing NT Server -- Pt. II. Components of a Solid NT Server System. 6. Building a Solid Server System. 7. Scaling Up Your NT System. 8. Optimizing Your Network Design. 9. Protecting Your Server from Power Failures. 10. Building Reliable and Efficient Mass Storage into NT Server. 11. Backing Up Your NT System. 12. Designing a Balanced System -- Pt. III. Networking and Security. 13. Planning and Managing Network Domains. 14. Setting Up NT Services for Microsoft Windows Clients. 15. Setting Up Macintosh Clients for NT Server.
Includes index.